Riau Folklore Theme Park Di Pekanbaru Dengan Penerapan Teknologi Simulator - Susilo, Bagus Ardyawan; Aldy, Pedia; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indoensia have various folk stories with any tittle and messages in the story, certainly become local wisdom in Indonesia. The story from every province in Indonesia, including in Riau province. But in nowadays, childern’s interests to folk story is decrease, folk story from abroad are very popular, for example Snow White and Cinderella. The ways can be do for take the memories interest people especially the children to Riau folk story by developt Theme Park which amusement park that tells about folk story in Riau. This theme park applying simulator technology so visitors can feel the atmosphere in the story from simulations on the amusement park. This folklore Theme Park applies the concept of "story of 4 Rivers". The concept selection that will be applied to this Theme Park is to choose based on folklore in Riau because the function of this building is Riau Folklore Theme Park, which is a theme park of Riau folklore. In this theme park visitors can get entertainment, children can get moral values to social values from the story and hoped after visiting this place children can apply these messages in their daily lives and can bring back their interest to Riau folk story. Keyword: Folklore, Theme Park, Simulator